Ab-Initio and Vibrational Studies on Free Base, Cationic and Derived from Antihistaminic Cyclizine Agent - Marquez, Maria J. (2019)
Experimental available infrared, Attenuated Total Reflectance (ATR) and Raman spectra of cyclizine hydrochloride have been employed to perform the complete assignments of expected 120, 123 and 126 vibration modes for free base, cationic and hydrochloride species of antihistaminic cyclizine (CYC) agent combining the Scaled Quantum Mechanical Force Field (SQMFF) methodology with Ab-initio calculations. The harmonic force fields and the force constants are reported for first time for those three species of CYC by using the B3LYP/6-31G* method. The predicted infrared, Raman and ultraviolet-visible spectra show reasonable correlations with the corresponding experimental ones. The most low solvation energy value was observed for the free base of CYC, as compared with the corresponding to scopolamine, heroin, morphine, cocaine and tropane alkaloids. The geometrical parameters predicted for the three cyclizine species show that both phenyl rings are symmetric, as evidenced from the experimental structure. The N-CH3 distances in the three species of CYC have showed that the free base in solution presents practically the same value than heroin and morphine in the same medium. This similarity in the values could be attributed to that in CYC the N-CH3 group is linked only to a ring(piperazine), as in heroin and morphine and not to bicyclic rings as in cocaine, scopolamine and tropane alkaloids. The mapped Molecular Electrostatic Potentials (MEP) surfaces reveal different nucleophilic and/or electrophilic regions in the three species of CYC where probable reactions can take place. Natural bond orbital (NBO) studies show clearly that the high stabilities of free base and hydrochloride species are strongly related to the * transitions due to the two phenyl rings in their structures while atoms in molecules (AIM) analyses clearly supports the high stability of hydrochloride species in solution due to the two interactions, H24---H30 and ionic H43---Cl44 interaction, where the strong ionic interaction is visibly evidenced by their highest values of their topological properties